2017
DOI: 10.3390/ijerph14091049
|View full text |Cite
|
Sign up to set email alerts
|

Association between Childhood Diarrhoeal Incidence and Climatic Factors in Urban and Rural Settings in the Health District of Mbour, Senegal

Abstract: We assessed the association between childhood diarrhoeal incidence and climatic factors in rural and urban settings in the health district of Mbour in western Senegal. We used monthly diarrhoeal case records among children under five years registered in 24 health facilities over a four-year period (2011–2014). Climatic data (i.e., daily temperature, night temperature and rainfall) for the same four-year period were obtained. We performed a negative binomial regression model to establish the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 52 publications
(67 reference statements)
3
25
0
1
Order By: Relevance
“…A significant association of non-cholera diarrhoea related hospital visits was found with high and low rainfall and with high temperature in Dhaka, Bangladesh [9]. In Senegal, there were two annual peaks in diarrhoeal incidence: one during the cold dry season and one during the rainy season [10]. Thiam et al [10] observed a positive association of diarrhoeal incidence with high average temperature of 36 • C and above, and high cumulative monthly rainfall at 57 mm and above in Senegal.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A significant association of non-cholera diarrhoea related hospital visits was found with high and low rainfall and with high temperature in Dhaka, Bangladesh [9]. In Senegal, there were two annual peaks in diarrhoeal incidence: one during the cold dry season and one during the rainy season [10]. Thiam et al [10] observed a positive association of diarrhoeal incidence with high average temperature of 36 • C and above, and high cumulative monthly rainfall at 57 mm and above in Senegal.…”
Section: Introductionmentioning
confidence: 94%
“…In Senegal, there were two annual peaks in diarrhoeal incidence: one during the cold dry season and one during the rainy season [10]. Thiam et al [10] observed a positive association of diarrhoeal incidence with high average temperature of 36 • C and above, and high cumulative monthly rainfall at 57 mm and above in Senegal. In Vietnam, considerable spatial heterogeneity existed in the risk of all-cause for diarrhoea across districts investigated with low elevation and differential responses to flooding and air temperature, and humidity further drove spatial heterogeneity in diarrhoeal disease risk [11].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the complex pathways linking climate anomalies and diarrhoea [69] and the challenges this poses for quantifying the effects of weather and climate on water-associated diseases in general [70][71][72], diarrhoeal illness is generally sensitive to climate anomalies [73][74][75][76][77][78] with unusually warm conditions conducive to enhanced pathogen replication and survival rates, while rainfall surpluses may transport faecal matter into water courses with micro-organisms becoming concentrated in water bodies during periods of rainfall deficit. While Demisse and Mengisitie [79] noted that El Niño has an impact on diarrhoea incidence for a number of major geographic regions, many of the cited papers address temperature/rainfall-diarrhoea association as opposed to climate driven variations in diarrhoea moderated by ENSO.…”
Section: Diarrhoeamentioning
confidence: 99%
“…Los fenómenos naturales y meteorológicos también pueden jugar un papel clave en la expansión o reducción geográfica de diferentes enfermedades; cuando nos referimos a fuerzas naturales implicadas en la aparición de brotes epidémicos usualmente pensamos en grandes catástrofes, como terremotos o tsunamis, pero también fenómenos meteorológicos como las estaciones húmedas y secas o frías y cálidas tienen un papel directo en la presencia y ausencia de algunas enfermedades (12,13) . Un ejemplo recurrente es el fenómeno de El Niño, que juega un papel clave en el desarrollo de brotes de enfermedades en Sudamérica y otras áreas (14,15) .…”
Section: Fenómenos Naturalesunclassified